PREFERENSI PENGHUNI PERUMAHAN DI KOTA PEKANBARU DALAM MENENTUKAN LOKASI PERUMAHAN - Febby Asteriani (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
Housing development at Pekanbaru city growth rapidly. The phenomenon is happening right now, housing spread sporadically almost all over town, until it is feared will monopolize the land developed. In determining the location of housing, the residents must have the important factors for consideration. This study aims to find out how the site selection factors according to the preferences housing residents. The research uses deductive approach with quantitative methods. The research started from theories that already exist, then look at the condition of the field. Research carried out on housing residents in 5 districts with most dominant amount of housing in Pekanbaru city for five years (2003-2007). The results showed that all the studies about the factors housing site selection are all factors that are considered to determine by housing residents in determining the location of housing, but not all sub-factors are elements that are considered by them.